An econometric analysis of the determinants of demand for palm oil in Nigeria - Egwuma, Henry; Shamsudin, Mad Nasir; Mohamed, Zainal Abidin; Kamarulzaman, Nitty Hirawaty; Wong, Kelly Kai Seng (Meghana Publications, 2016)
This paper empirically examines the determinants of palm oil demand in Nigeria. Within a time series framework, we adopted the Autoregressive Distributed Lag (ARDL) technique to establish the presence of long-run relationships between palm oil demand and its determinants. We find compelling evidence for the existence of a cointegrating relationship between the variables of interest. Our results further reveal that the price of palm oil and income are the major drivers of both import and domestic demand for palm oil in Nigeria. The study recommends that macroeconomic stabilization strategies and appropriate pricing policies should be designed to ensure the expansion of palm oil market share.